Analysis of Stock Exchange Selection Strategy to Go Public and Its Impact on Company Growth - Afdal, Muhammad; Amalianty, Nur; Madjid, Arifin H.A (Advances in Management & Financial Reporting, 2025)
Purpose: This study analyzes the strategic impact of stock exchange selection on companies going public and its influence on long-term growth. It focuses on how exchange choice affects access to capital, corporate reputation, governance practices, and financial performance. Research Method: This study adopts a qualitative approach, utilizing a systematic literature review (SLR) methodology. The research synthesizes existing literature from peer-reviewed articles, reports, and studies, focusing on the factors influencing stock exchange selection and its subsequent effects on company growth and performance. Results and Discussion: The findings reveal that exchanges with high liquidity and strong reputations, such as NYSE and NASDAQ, provide companies with greater access to capital and a broader investor base. The study also demonstrates that listing on reputable exchanges enhances corporate governance, improves market visibility, and supports long-term growth through strategic alignment with sector-specific growth and diversification. Regulatory frameworks and governance standards are critical in fostering investor trust and market stability. Implications: The research has significant practical implications for companies considering IPOs. It underscores the importance of selecting exchanges that align with growth strategies, regulatory standards, and long-term goals. Companies should prioritize exchanges with high liquidity and robust governance structures to attract institutional investors and expand their international presence. The study also provides managers with insights into making informed decisions about exchange selection, based on long-term growth and strategic alignment.